Recent updates of interferon-derived myxovirus resistance protein A as a biomarker for acute viral infection - Desalegn Abebaw; Yibeltal Akelew; Adane Adugna; Zigale Hibstu Teffera; Habtamu Belew; Bantegzie Selabat; Molla Getie; Anemut Tilahun Mulu; Aytenew Atnaf (European Journal of Medical Research)
Abstract Background Antibiotic resistance (AMR) remains a global public health threat with a high burden in sub-Saharan countries. The overuse of antimicrobials in the clinical setting is the main factor for the spread of antibiotic resistance. Diagnostic uncertainty in differentiating between bacterial and viral infections is the major contributor to antimicrobial overuse. The available biomarkers lack specificity in guiding clinicians to make antibiotic decisions and only estimate bacterial infection. Main body Myxovirus resistance (Mx) proteins are a type of interferon (IFN)-inducible protein that belongs to the dynamin superfamily of large guanine triphosphates (GTPases) involved in broad antiviral responses. Myxovirus resistance protein A (MxA) is a host-derived biomarker with antiviral properties against various viruses. It is induced by IFN I and IFN III as part of the innate immune response. Its basal level is < 15 ng/ml and elevated levels are detectable 1–2 h after IFN induction and remain detectable in serum up to 10 days after viral infection. Increased levels in the blood are associated with viral infection and remain low during bacterial infections. This biomarker showed promising performance in diagnosing undifferentiated febrile patients with respiratory tract infections. In this review, we discuss the role of Mx proteins, specifically MxA, in diagnosing acute viral infections, including how they are induced and their potential as diagnostic tools. Methods A comprehensive electronic search was conducted in Scopus and Medline (using the PubMed interface) regarding myxovirus resistance protein A as a biomarker for acute viral infection. In the search strategy, English language was used without date restriction. Manual search was also performed when appropriate. Conclusions Elevated MxA combined with other biomarkers, such as CRP and PCT, is a promising tool for identifying patients with viral infections. Therefore, incorporating MxA in the existing point of care formats help to improve the antibiotic stewardship programs and future randomized controlled trials are recommended to evaluate its utility in medical practice.